Synthesis and α-Functionalisation of Cyclic Imines - Kuang, Ze; Ding, Xiao-Bo; Furkert, Daniel P.; Brimble, Margaret A. (Synlett, 2024)
α-Functionalisation of cyclic imines is explored. The cyclic imine substrates are synthesised from their respective halonitrile precursors using a nucleophilic addition/cyclisation sequence. Selective monohalogenation of the cyclic imines yields α-haloimines, which serve as a platform to obtain various α-hydroxyimine derivatives. In addition, an unusual tautomerisation and oxidation sequence is observed in the attempted preparation of α-hydroxyimines.
Keywords: cyclic imine; spiroimine; α-functionalisation; α-hydroxyimine; α-bromoimine